Normal hand grip strength in the adult Malaysian population - Kamarul, Tunku; Ahmad, T.S.; Loh, W.Y.C. (SAGE Publications (UK and US), 2006)
PURPOSE: To measure the hand grip strength of Malaysians aged 18 to 65 years. METHODS: Between January and April 2003, 412 subjects (200 women and 212 men) were recruited from staff, students, and visitors of the University of Malaya Medical Centre. Socioeconomic, general health, and lifestyle data were collected from each subject using a standard questionnaire. Weight and height were measured prior to testing. Standardised positioning and instructions based on several hand grip protocols were used. Data were collected using the LIDO kinetic work set. RESULTS: 93 of the subjects were right-hand dominant and 7 were left-hand dominant. Hand grip strength was significantly correlated with hand dominance, gender, occupation, height, and weight, but not body mass index. No significant differences in grip strength were noted with regard to race or level of income. Men were stronger than women in all age-groups, with a ratio of 1.75:1. In both right- and left-hand dominant groups, the dominant hand was consistently stronger than the non-dominant side, with a ratio of 1.12:1 in the right-hand dominant group and 1.05:1 in the left-hand dominant group. The strongest hand grip strength in the right-hand dominant group occurred in the age-group of 25 to 34 years; in the left-hand dominant group it was in the age-group of 18 to 24 years. In western populations, the mean grip strength can be as much as 1.5 times greater than in the Malaysian population. CONCLUSION: Data derived from western populations cannot be applied to a comparable Malaysian population. Gender, hand dominance, age, occupation, weight, and height must be considered when establishing normal values for grip strength.